Analisis Kelayakan Usaha Budidaya Udang Vaname Menuju Agriculture yang Berkelanjutan Di Kecamatan Buayan Kabupaten Kebumen (Studi Kasus Di Tambak Udang Jladri): Feasibility Analysis of Vaname Shrimp Cultivation Business Towards Sustainable Agriculture in Buayan District, Kebumen Regency (Case Study in Jladri Shrimp Pond) - Basuki, Awaludin Yusuf; Muh Widodo, Eko; Rifai, Affan (Universitas Muhammadiyah Magelang, 2025)
Jladri Shrimp Farm is a shrimp farm that has promising economic prospects, especially as Indonesia's leading export commodity. This pond faces various challenges from technical, economic and environmental aspects that can affect its sustainability. This study aims to analyze the feasibility of Vaname shrimp farming in Jladri Shrimp Pond based on these three aspects in order to provide recommendations for sustainable business development. The results showed that technically, this farm has an average Survival Rate (SR) value above 70%, which indicates a good Survival Rate of shrimp, as well as Feed Conversion Ratio (FCR) values ranging from 0.85 to 1.1, which indicates optimal feed efficiency. From an economic point to view, significant results were obtained as evidenced by the Payback Period of 1 year 6 months 14 days, a positive Net Present Value (NPV) of Rp 7,516,119,200, a Profitability Index (PI) of 7.54, and an Internal Rate of Return (IRR) of 111%. However, the environmental assessment showed that carbon emissions from electricity and fuel consumption exceeded the standards set, indicating the need for increased energy efficiency and the use of renewable energy to reduce environmental impacts and improve the sustainability of shrimp farming.